The parasitic worm product ES-62 protects against collagen-induced arthritis by resetting the gut-bone marrow axis in a microbiome-dependent manner - Harnett, Margaret M.; Doonan, James; Tarafdar, Anuradha; Pineda, Miguel A.; Duncombe-Moore, Josephine; Buitrago, Geraldine; Pan, Piaopiao; Hoskisson, Paul A.; Selman, Colin; Harnett, William (Frontiers in Tropical Diseases, 2024)
The parasitic worm-derived immunomodulator, ES-62 rescues defective levels of IL-10-producing regulatory B cells (Bregs) and suppresses chronic Th1/Th17-driven inflammation to protect against joint destruction in the mouse collagen-induced arthritis (CIA) model of rheumatoid arthritis. Such autoimmune arthritis is also associated with dysbiosis of the gut microbiota and disruption of intestinal barrier integrity. We recently further exploited the CIA model to show that ES-62’s prevention of joint destruction is associated with protection of intestinal barrier integrity and normalization of the gut microbiota, thereby suppressing the gut pathology that precedes the onset of autoimmunity and joint damage in CIA-mice. As the status of the gut microbiota impacts on immune responses by influencing haematopoiesis, we have therefore investigated whether ES-62 harnesses the homeostatic mechanisms regulating this gut-bone marrow (BM) axis to resolve the chronic inflammation promoting autoimmunity and joint destruction in CIA. Reflecting this, ES-62 was found to counteract the BM myeloid/lymphoid bias typically associated with chronic inflammation and infection. This was achieved primarily by ES-62 acting to maintain the levels of lymphoid lineages (B220+ and CD3+ cells) observed in naïve, healthy mice but lost from the BM of CIA-mice. Moreover, ES-62’s ability to prevent bone-destroying osteoclastogenesis was found to be associated with its suppression of CIA-induced upregulation of osteoclast progenitors (OCPs) in the BM. Critically, and supporting ES-62’s targeting of the gut-BM axis, this rewiring of inflammatory haematopoiesis was lost in mice with a depleted microbiome. Underlining the importance of ES-62’s actions in restoring steady-state haematopoiesis, the BM levels of B and T lymphoid cells were shown to be inversely correlated, whilst the levels of OCPs positively correlated, with the severity of joint damage in CIA-mice.